The Influence of Product Bundling And Live Streaming on The Purchase Intention of Somethinc Products on Gen Z In Kediri City With Influenser as a Moderating Variable - Sary, Acsho Lesisthree Purnama; S, Beny Mahyudi; Syahputra, Erwin (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to examine the effect of product bundling and live streaming on purchase intention through influencers as moderating variables. The object of this research is aimed at gen Z in Kediri City. Sampling was carried out using purposive sampling technique, with a total sample of 100 samples, which were distributed to gen Z in Kediri City. The instrument in this study used a questionnaire with a Likert scale using SmartPLS software for the analysis tool. The results of this study indicate that, 1) Product bundling has a positive and significant influence on purchase intention; 2) Live streaming also has a positive but insignificant effect on purchase intention; 3) Influencers have a positive and significant effect on purchase intention; 4) Influencers significantly strengthen the effect of bundling products on purchase intention; 5) Influencers have a significant effect but are unable to strengthen the relationship between live streaming and purchase intention